Implementasi Cloud-Based Monitoring and Control System pada Automatic Transfer Switch (ATS) - Mohammad Dahlan; Noor Yulita dwi Setianingsih; Budi Cahyo Wibowo (Simetris: Jurnal Teknik Mesin, Elektro dan Ilmu Komputer, 2026)
Dependence on a reliable electricity supply drives the need for a system that can automatically switch to a backup power source (generator) when the main supply (PLN) experiences a disruption. This study designed an Automatic Transfer Switch (ATS) that not only functions automatically but can also be monitored remotely. The ATS system was designed using a NodeMCU ESP32 as the main controller. The PZEM004T sensor is used to monitor the PLN voltage. This system can operate in automatic and manual modes. Data from the sensor is sent to a server via Wi-Fi to be displayed on a monitoring website in real-time. Test results proved that the system functioned well. The average power source switching response time was 4-6 seconds in automatic mode and 6 seconds in manual mode. The NodeMCU ESP32 successfully processed sensor data, controlled the relay, and sent data to the server. The Wi-Fi connection was effective up to a distance of 20 meters with an average initialization time of 10 seconds. This system has proven to be able to maintain the continuity of the electricity supply while facilitating remote monitoring.